Math Problem Statement

Given a linear time-invariant system S with input-output relationships: x(t) = e^(j2t) -> y(t) = e^(j3t) and x(t) = e^(-j2t) -> y(t) = e^(-j3t). Compute the outputs corresponding to x1(t) = cos(2t) and x2(t) = cos(2(t - 1/2)).

Solution

The image contains a system of equations and problems related to signal processing in the time domain. Let’s break this down step by step:

  1. Given System:

    • The system SS takes input x(t)x(t) and gives output y(t)y(t) with different responses for ej2te^{j2t} and ej2te^{-j2t}.

      For x(t)=ej2tx(t) = e^{j2t}, y(t)=ej3ty(t) = e^{j3t}.

      For x(t)=ej2tx(t) = e^{-j2t}, y(t)=ej3ty(t) = e^{-j3t}.

  2. Tasks:

    • (a)(a) Compute the output y(t)y(t) corresponding to x1(t)=cos(2t)x_1(t) = \cos(2t).
    • (b)(b) Compute the output y(t)y(t) corresponding to x2(t)=cos(2(t12))x_2(t) = \cos\left(2\left(t - \frac{1}{2}\right)\right).

Solution:

(a) For x1(t)=cos(2t)x_1(t) = \cos(2t):

  • Using Euler's formula: cos(2t)=12(ej2t+ej2t)\cos(2t) = \frac{1}{2}\left(e^{j2t} + e^{-j2t}\right).
  • The system is linear, so the output y1(t)y_1(t) is the sum of the outputs for ej2te^{j2t} and ej2te^{-j2t}: y1(t)=12(S(ej2t)+S(ej2t))y_1(t) = \frac{1}{2}\left(S(e^{j2t}) + S(e^{-j2t})\right)
  • Substitute the responses: S(ej2t)=ej3t,S(ej2t)=ej3t.S(e^{j2t}) = e^{j3t}, \quad S(e^{-j2t}) = e^{-j3t}.
  • Thus: y1(t)=12(ej3t+ej3t)=cos(3t).y_1(t) = \frac{1}{2}\left(e^{j3t} + e^{-j3t}\right) = \cos(3t).
  • Final result for (a): y1(t)=cos(3t)y_1(t) = \cos(3t).

(b) For x2(t)=cos(2(t12))x_2(t) = \cos\left(2\left(t - \frac{1}{2}\right)\right):

  • Using the time-shifting property: cos(2(t12))=12(ej2(t1/2)+ej2(t1/2))\cos\left(2\left(t - \frac{1}{2}\right)\right) = \frac{1}{2}\left(e^{j2(t - 1/2)} + e^{-j2(t - 1/2)}\right).
  • Expanding:
### Solution Continued:

Expanding for x2(t)=cos(2(t12))x_2(t) = \cos\left(2\left(t - \frac{1}{2}\right)\right):

(b) Deriving y2(t)y_2(t):

Using the time-shifted input:

[ x_2(t) = \cos\left(2\left(t - \frac{1}{2}\right)\right) = \frac{1}{2}\left(e^{j2t}e^{-j} + e^{-j2t}e^{j}\right).$$

  1. Apply the linearity of the system SS:

    • The input ej2teje^{j2t}e^{-j} has the response S(ej2t)=ej3tS(e^{j2t}) = e^{j3t}, so: S(ej2tej)=ej3tej=ej(3t1).S(e^{j2t}e^{-j}) = e^{j3t}e^{-j} = e^{j(3t - 1)}.
    • Similarly, the input ej2teje^{-j2t}e^{j} has the response S(ej2t)=ej3tS(e^{-j2t}) = e^{-j3t}, so: S(ej2tej)=ej3tej=ej(3t1).S(e^{-j2t}e^{j}) = e^{-j3t}e^{j} = e^{-j(3t - 1)}.
  2. Combine the results:

    • The output is: y2(t)=12(ej(3t1)+ej(3t1)).y_2(t) = \frac{1}{2}\left(e^{j(3t - 1)} + e^{-j(3t - 1)}\right).
  3. Simplify using Euler's formula: y2(t)=cos(3(t13)).y_2(t) = \cos\left(3\left(t - \frac{1}{3}\right)\right).

Final Results:

  • (a) y1(t)=cos(3t)y_1(t) = \cos(3t).
  • (b) y2(t)=cos(3(t13))y_2(t) = \cos\left(3\left(t - \frac{1}{3}\right)\right).

Do you have any further questions or would like detailed explanations on specific steps? Here are 5 related questions to consider:

  1. How does the system's linearity affect the computation of outputs for superimposed signals?
  2. What is the significance of the time-shifting property in solving (b)?
  3. Can you explain the difference between ejωte^{j\omega t} and cos(ωt)\cos(\omega t) in this context?
  4. How would the solution change if the system's response were nonlinear?
  5. What role does Euler's formula play in solving these problems efficiently?

Tip: When working with signals in the frequency domain, always verify the linearity and time-invariance properties to simplify the calculations.

Ask a new question for Free

By Image

Drop file here or Click Here to upload

Math Problem Analysis

Mathematical Concepts

Signal Processing
Linear Systems
Fourier Analysis

Formulas

Euler's Formula: cos(ωt) = (1/2)(e^(jωt) + e^(-jωt))
System Linearity: S(ax1(t) + bx2(t)) = aS(x1(t)) + bS(x2(t))
Time-shifting property: x(t - t0) <-> X(f)e^(-j2πft0)

Theorems

Linearity of Linear Time-Invariant Systems

Suitable Grade Level

Undergraduate - Electrical Engineering or Mathematics